Korean Drama Blind: Analysis Using Charles S. Peirce's Mutually Exclusive Theory (Cinematology: Journal Anthology of Film and Television Studies, 2024)
Korean drama or Drakor is one of the shows that is popular with various groups. One of the dramas that has a high rating in 2022 is entitled "Blind". With the mystery-detective genre, this drama has many plot twists. Tells about a typical murder, and the killer asks for a jury trial. The jury summoned for the trial consisted of seven people. The main characters in this drama are Ryu Sung Hoon as the judge from this specialty, Ryu Sung Joon, the judge's younger brother who is the detective in this case, and Eun Ki, a social worker and one of the seven trial jurors.In storytelling, of course there will be choices to build the narrative, this can be called the mutually exclusive theory. Mutually exclusive itself is an event whose occurrence cannot occur simultaneously at the same time. Indirectly here it is explained that there will be two or more choices or events that cannot occur simultaneously at the same time. So there must be something chosen and left behind, there will be things that will happen and things that will not happen. By using the mutually exclusive theory the author will apply it to the drama Blind. In almost every episode the character will be faced with various plots and choices and he can only choose one of these choices at the same time.